(untitled) (Medical Forum Monthly, 2024)
Objective: The purpose of this study was to compare the role of time management skills among academic and administrative staff in an institute Study Design: Descriptive Study Place and Duration of Study: This study was conducted at a Army Medical College, Rawalpindi from July 2015 to September 2015 Materials and Methods: Fifty participants were selected through random sampling. After the informed consent the questionnaire was given to the administration and faculty staff of the public sector medical college. Questionnaire based survey was conducted to collect data regarding demographic, awareness about time management and practices to manage time effectively at the institution. Does their organization observe active time management? Has time execution effectively been useful in the accomplishment of their set objectives? Does interaction with the difficult people, role of procrastination and appropriate scheduling effects the effective time management. Results: Twenty-eight (fifty six percent) males and twenty-two (forty four percent) females with mean age of 43.54±7.58 participated in the study. Four (eight percent) were not married and 46(ninety two percent) were married. Mean job experience of the participants was 17.55±7.36 Conclusion: The awareness and perception of the both the genders regarding the effective time management factors is important to plan and execute institute management